2020
DOI: 10.1109/twc.2020.2988001
|View full text |Cite
|
Sign up to set email alerts
|

On the Performance Gain of Harnessing Non-Line-of-Sight Propagation for Visible Light-Based Positioning

Abstract: Visible light signals undergo non-line-of-sight (NLOS) propagation, and the NLOS links are usually treated as disturbance sources in conventional visible light-based positioning (VLP) methods to simplify signal processing. However, the impact of NLOS propagation on the VLP performance is not fully understood. In this paper, we shall reveal the performance limits of VLP systems under diffuse scattering. First, the closed-form Cramer-Raw lower bounds (CRLBs) on the estimate errors of user detector (UD) location … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 45 publications
(97 reference statements)
0
6
0
Order By: Relevance
“…However, these SPAO methods [10]- [19], [22]- [27] consider a line-of-sight (LOS) scenario, and hence scattering interference and random fading are unresolved, which are major error sources that cannot be safely ignored in VLP [28]- [33].…”
Section: A Research Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these SPAO methods [10]- [19], [22]- [27] consider a line-of-sight (LOS) scenario, and hence scattering interference and random fading are unresolved, which are major error sources that cannot be safely ignored in VLP [28]- [33].…”
Section: A Research Motivationmentioning
confidence: 99%
“…In summary, it is concluded in [24] and [28] that geometric intersection and LRM-driven VLP performance will be seriously degraded by scattering interference, especially in a high signal-to-noise ratio (SNR) environment. Moreover, VLP also suffers from random fading due to uncertain reflection rate and variant environments.…”
Section: A Research Motivationmentioning
confidence: 99%
“…This is mainly due to the fact that the expression of the NLOS channel gain w.r.t the UE location and orientation is complex, and hence, it could not be handled straightforwardly in an optimization fashion. However, it was shown recently in [32] that LiFi systems can gain additional UE position and orientation information from the NLOS links via leveraging the NLOS propagation knowledge. Specifically, the closed-form Cramer-Raw lower bounds (CRLBs) on the estimation errors of the UE location and orientation, are derived.…”
Section: B Existing Solutionsmentioning
confidence: 99%
“…To minimize errors, Lekkas et al employed statistical testing to assess the quality distribution of observed values, thus improving positioning accuracy [21]. Furthermore, nonlinear iterative methods include Fang, SX, SI, and Taylor series expansions [22,23]. To reduce the location bias and improve location accuracy, Liang et al presented a novel bias-reduced method based on an iterative constrained weighted least squares algorithm [24].…”
Section: Introductionmentioning
confidence: 99%